Polymorphism at variable regions (VRs) of porA gene from Neisseria meningitidis strains isolated in Northern Vietnam - Xuan Thach, Tran; Thu Trang, Le; Phi Long, Trieu; Hoa, Nguyen Thi; Quyen, Dong Van; Minh Huong, Nguyen (Vietnam Journal of Biotechnology, 2020)
Meningococcal bacterium Neisseria meningitidis is one of the major causes of meningitis worldwide. Currently in Vietnam, N. meningitidis B and C are the most prevalent invasive serogroups. N. meningitidis expresses two major transmembrane proteins, PorA and PorB, of which PorA showed high levels of polymorphism among strains and has been studied as one component of vaccines against N. meningitidis B. Polymorphisms in porA gene clustered into three variable regions VR1, VR2 and VR3. In this study, we sequenced the entired porA gene of 19 N. meningitidis strains isolated from military units in northern Vietnam during the period 2008 – 2017 in order to: (1) evaluate the polymorphism of porA gene at nucleotide level and predict its immuno-reactivity from annotated amino acide sequences; and (2) compare porA variants of Vietnamese strains with known strains worldwide. Our results showed a high level of polymorphisms among Vietnamese strains, with the highest polymorphism found in VR1, followed by VR2 and VR3. Notably, 5/19 strains in this study showed novel variants at VR2 with unknown immunological reactivity. This result suggested potential novel immunological characteristics of meningococcal strains from Vietnam.